THE POWER OF PSYCHOLOGICAL CONGRUENCE IN DRIVING IMPULSE BUYING ON SOCIAL PLATFORMS - Brillyan Rizqi; Nia`` Kurniawati; Yolanda Masnita; Nisa Andini Faradina (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study examined the influence of self-congruence—both consumer–product and consumer–influencer congruence—on online impulse buying intention (OIBI), with consumer confidence as a mediating variable. A total of 239 Indonesian social commerce users participated in the survey, and the data were analyzed using PLS-SEM. The findings showed that both consumer–product and influencer–product congruence significantly affected OIBI, while consumer confidence did not act as a significant mediator. Interestingly, consumer–influencer congruence only influenced impulse buying through confidence, not directly. These results suggested that symbolic fit with influencers and products played a stronger role in impulsive buying than internal confidence.